Synthesis of N‐(phenoxyalkyl)‐, N‐2‐[2‐(phenoxy)ethoxy]ethyl‐ or N‐(phenoxyacetyl)piperazine Derivatives and Their Activity Within the Central Nervous System. Issue 32 (27th August 2019) - Pańczyk, Katarzyna; Pytka, Karolina; Jakubczyk, Magdalena; Rapacz, Anna; Siwek, Agata; Głuch‐Lutwin, Monika; Gryboś, Anna; Słoczyńska, Karolina; Koczurkiewicz, Paulina; Ryszawy, Damian; Pękala, Elżbieta; Budziszewska, Bogusława; et al.
Abstract: Depression, anxiety and epilepsy share some etiology factors, causing frequently observed multimodal activity of centrally active compounds. This might raise the risk of central adverse effects of potential drugs, but on the other hand ‐ in a light of common comorbidity of these diseases ‐ also make an opportunity for avoiding polypragmasy. The presented study combines rational drug design methods, chemical synthesis, receptor studies and in vivo pharmacological screening (mice, i. p .) in order to obtain new centrally active piperazine derivatives in a context of their potential multimodality, investigate the mechanism of their activity and establish relationship between their structure, molecular mechanism and in vivo central activity(‐ies). The most promising pharmacological profile showed 1‐(2‐(2, 5‐dimethylphenoxy)ethyl)‐4‐phenylpiperazine dihydrochloride (1 ), which was active in the four‐plate test (anxiolytic‐like activity) at 1.25 mg/kg b.w. and possessed high affinities towards several tested molecular targets (5‐HT1A K i =35 nM ‐ weak antagonist, 5‐HT2A K i =121 nM, 5‐HT7 K i =130 nM ‐ weak antagonist, α1 K i =82 nM, μ K i =240 nM). Abstract : N ‐(phenoxyalkyl) derivatives of piperazine as multitarget centrally active compounds: In a series of potentially centrally active arylpiperazine derivatives a potent anxiolytic compound was identified. Broad panel of receptor studies revealed its possible mechanism of action and preliminary safety studies proved its utility as a drug candidate or staring point for further structural modifications.